A Review Study on Effectiveness of Project-Based Learning on Mathematical Achievement - Pathak, Bhawani (Okhaldhunga Journal, 2024)
This is a review study based on various selected articles. In this study, literature has been analyzed by the narrative review method. This study focuses on the characteristics of Project-based learning (PBL), steps of Project-based learning, strengths of Project-based learning, and challenges of Project-based learning in mathematics. Project-based learning gives the opportunities to the learner to explore the idea, gather different information and develop new skills and knowledge. PBL supports developing the skill of problem-solving, enhancing collaborative learning, developing the ability to creative thinking and construct new knowledge, developing social interaction and communication skills, and developing the level of confidence to solve the problem.